The Effect of Profit Behavior and Tax Aggressiveness After The Impelementation of PSAK 73: Literature Review - Aulia, Estin Zahwa; Alvia, Liza (PT FORMOSA CENDEKIA GLOBAL, 2024)
This article aims to present a literature review related to research that discusses the impact of the implementation of PSAK 73, especially on profit behavior and tax aggressiveness. PSAK 73 is a new regulation that was implemented effectively on January 1, 2020, so this change is still a hot issue to be discussed. This literature review contains articles from 2018 to 2023. This article shows that there are still differences in results related to profit behavior, which shows an increase and decrease in profits. Meanwhile, for tax aggressiveness behavior some studies show influence and some show no effect on the level of tax aggressiveness.